Interactive fuzzy optimization for an economic and environmental balance in a river system - Lee, Chih-Sheng; Chang, Shui-Ping (Water research (Oxford), 2005)
An interactive fuzzy approach is applied to develop a water quality management plan in a river basin for solving multi-objective optimization problems involving vague and imprecise information related to data, model formulation, and the decision maker's preferences. This approach, originally proposed by Sakawa in 1983, is modified and presented as a sustainable water quality management strategy in which the decision makers and the environmental analysts put forward their views on three major economic and environmental factors: river water quality, assimilative capacity, and treatment cost of wastewater. This methodology is illustrated in a case study of multi-objective water quality management in the Tou-Chen River Basin in northern Taiwan. The incorporation of these three economic and environmental factors demonstrates the capability of the fuzzy interactive multi-objective optimization approach and also works suitably in water quality management in a river basin by the trade-off procedures.